The manifestation of the religiosity of older people through social media during the pandemic period - Chirugu, Gianina; Damean, Doru Claudiu (Technium Social Sciences Journal, 2022)
The analysis of the manifestation of the religiosity of the elderly during the pandemic through social networks represents the object of this paper. In order to achieve the purpose of the research carried out involved the use of qualitative research methods the semi-structured interview and the case study, with the objective of having an overall view on this subject, having as a basis the revision of the works in international databases so as to obtain as much truthful information as possible for the scientific approach. In carrying out the qualitative research, 150 elderly people from Romania participated and the case study was carried out in Constanta because the Orthodox Church had an intense activity during the online pandemic. Different understandings of religion, church, and community were analyzed during a pandemic period and support the value of an approach that places debates born in the context of historical precedent, personal experience, and theoretical approaches to networks, communities, religion, and social media.